Implementing Multimedia-Based Integrated Learning of Concrete Construction and Entrepreneurship to Improve the Students’ Entrepreneurial Spirit - V. Lilik Hariyanto; Amat Jaedun; Nuryadin Eko Rahardjo; Faqih Ma'arif (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The objectives of the study were: (1) to formulate a multimedia-based integrated learning model of concrete construction and entrepreneurship and, (2) to measure the improvement of the students’ entrepreneurial spiritby implementing this developed integrated learning model in the classroom. This study was classified as a quasi-experimental study with a non-equivalent control group design. A pretest, treatment, andposttest were presented to the experimental and control groups. This study was conducted in 8 meetings at the Stone Installation and Concrete Constructionworkshop, Universitas Negeri Yogyakarta. Data were collected through tests to measure students' competence in entrepreneurship and Concrete Construction. The Concrete Construction skills were measured through product assessment. Testing of the validity and the reliability of the instruments used expert judgment and Cronbach Alpa respectively. Data were analyzed with a statistical t-test, with consideration of (a) the data normality, and (2) the homogeneity for the variance of each data group. This study concluded: (1) the integrated learning model was successfully formulated (2) there were positive and significant differences in the students' entrepreneurial spirit between the students treated with the developed integrated learning model and the students treated with the conventional learning model.